A “Cell-Friendly” Window for the Interaction of Cells with Hyaluronic Acid/Poly-l-Lysine Multilayers - Madaboosi, Narayanan; Uhlig, Katja; Schmidt, Stephan; Vikulina, Anna S.; Moehwald, Helmuth; Duschl, Claus; Volodkin, Dmitry (Macromolecular Bioscience, 2018)
Polyelectrolyte multilayers assembled from hyaluronic acid (HA) and poly-l-lysine (PLL) are most widely studied showing excellent reservoir characteristics to host molecules of diverse nature; however, thick (HA/PLL)n films are often found cell repellent. By a systematic study of the adhesion and proliferation of various cells as a function of bilayer number “n” a correlation with the mechanical and chemical properties of films is developed. The following cell lines have been studied: mouse 3T3 and L929 fibroblasts, human foreskin primary fibroblasts VH-Fib, human embryonic kidney HEK-293, human bone cell line U-2-OS, Chinese hamster ovary CHO-K and mouse embryonic stem cells. All cells adhere and spread well in a narrow “cell-friendly” window identify in the range of n = 12–15. At n < 12, the film is inhomogeneous and at n > 15, the film is cell repellent for all cell lines. Cellular adhesion correlates with the mechanical properties of the films showing that softer films at higher “n” number exhibiting a significant decrease of the Young's modulus below 100 kPa are weakly adherent to cells. This trend cannot be reversed even by coating a strong cell-adhesive protein fibronectin onto the film. This indicates that mechanical cues plays a major role for cell behavior, also in respect to biochemical ones.
CRIS-Team Scopus Importer:2021-06-08
Keywords: cell adhesion; colloidal probe; layer-by-layer; softness; Young's modulus

A lipid membrane supported on an artificial extracellular matrix made of polyelectrolyte multilayers: towards nanoarchitectonics at the cellular interface - Vikulina, Anna; Wulf, Alena; Guday, Guy; Fakhrullin, Rawil; Volodkin, Dmitry (Nanoscale, 2022)
To implement a specific function, cells recognize multiple physical and chemical cues and exhibit molecular responses at their interfaces - the boundary regions between the cell lipid-based membrane and the surrounding extracellular matrix (ECM). Mimicking the cellular external microenvironment presents a big challenge in nanoarchitectonics due to the complexity of the ECM and lipid membrane fragility. This study reports an approach for the assembly of a lipid bilayer, mimicking the cellular membrane, placed on top of a polyelectrolyte multilayer cushion made of hyaluronic acid and poly-l-lysine - a nanostructured biomaterial, which represents a 3D artificial ECM. Model proteins, lysozyme and alpha-lactalbumin, (which have similar molecular masses but carry opposite net charges) have been employed as soluble signalling molecules to probe their interaction with these hybrids. The formation of a lipid bilayer and the intermolecular interactions in the hybrid structure are monitored using a quartz crystal microbalance and confocal fluorescence microscopy. Electrostatic interactions between poly-l-lysine and the externally added proteins govern the transport of proteins into the hybrid. Designed ECM-cell mimicking hybrids open up new avenues for modelling a broad range of cell membranes and ECM and their associated phenomena, which can be used as a tool for synthetic biology and drug screening.
CRIS-Team WoS Importer:2023-01-27

A mitochondrial pathway for biosynthesis of lipid mediators - Tyurina, Yulia Y.; Poloyac, Samuel M.; Tyurin, Vladimir A.; Kapralov, Alexander A.; Jiang, Jianfei; Anthonymuthu, Tamil Selvan; Kapralova, Valentina I.; Vikulina, Anna S.; Jung, Mi-Yeon; Epperly, Michael W.; Mohammadyani, Dariush; Klein-Seetharaman, Judith; et al. (Nature chemistry, 2014)
The central role of mitochondria in metabolic pathways and in cell-death mechanisms requires sophisticated signalling systems. Essential in this signalling process is an array of lipid mediators derived from polyunsaturated fatty acids. However, the molecular machinery for the production of oxygenated polyunsaturated fatty acids is localized in the cytosol and their biosynthesis has not been identified in mitochondria. Here we report that a range of diversified polyunsaturated molecular species derived from a mitochondria-specific phospholipid, cardiolipin (CL), is oxidized by the intermembrane-space haemoprotein, cytochrome c. We show that a number of oxygenated CL species undergo phospholipase A 2 -catalysed hydrolysis and thus generate multiple oxygenated fatty acids, including well-known lipid mediators. This represents a new biosynthetic pathway for lipid mediators. We demonstrate that this pathway, which includes the oxidation of polyunsaturated CLs and accumulation of their hydrolysis products (oxygenated linoleic, arachidonic acids and monolysocardiolipins), is activated in vivo after acute tissue injury. © 2014 Macmillan Publishers Limited.
CRIS-Team Scopus Importer:2021-06-08

Binding Mechanism of the Model Charged Dye Carboxyfluorescein to Hyaluronan/Polylysine Multilayers - Prokopovic, Vladimir Z.; Vikulina, Anna S.; Sustr, David; Shchukina, Elena M.; Shchukin, Dmitry G.; Volodkin, Dmitry V. (ACS Applied Materials and Interfaces, 2017)
Biopolymer-based multilayers become more and more attractive due to the vast span of biological application they can be used for, e.g., implant coatings, cell culture supports, scaffolds. Multilayers have demonstrated superior capability to store enormous amounts of small charged molecules, such as drugs, and release them in a controlled manner; however, the binding mechanism for drug loading into the multilayers is still poorly understood. Here we focus on this mechanism using model hyaluronan/polylysine (HA/PLL) multilayers and a model charged dye, carboxyfluorescein (CF). We found that CF reaches a concentration of 13 mM in the multilayers that by far exceeds its solubility in water. The high loading is not related to the aggregation of CF in the multilayers. In the multilayers, CF molecules bind to free amino groups of PLL; however, intermolecular CF-CF interactions also play a role and (i) endow the binding with a cooperative nature and (ii) result in polyadsorption of CF molecules, as proven by fitting of the adsorption isotherm using the BET model. Analysis of CF mobility in the multilayers by fluorescence recovery after photobleaching has revealed that CF diffusion in the multilayers is likely a result of both jumping of CF molecules from one amino group to another and movement, together with a PLL chain being bound to it. We believe that this study may help in the design of tailor-made multilayers that act as advanced drug delivery platforms for a variety of bioapplications where high loading and controlled release are strongly desired.
CRIS-Team Scopus Importer:2021-06-08
Keywords: adsorption isotherm; diffusion; fluorescence recovery after photobleaching; hyaluronic acid; layer-by-layer; polyadsorption

Bioactivity of catalase loaded into vaterite CaCO3 crystals via adsorption and co-synthesis - Feoktistova, Natalia A.; Vikulina, Anna S.; Balabushevich, Nadezhda G.; Skirtach, Andre G.; Volodkin, Dmitry (Materials & Design, 2020)
Protein therapy gained a reputation of the most direct and safe approach for treating various diseases, yet biodegradation and loss of bioactivity of fragile therapeutic proteins limit their wide medical use. Recently, a new hard templating technology using decomposable mesoporous vaterite CaCO3 crystals became extremely popular strategy for formulation of protein nano(micro)-vectors. This study deciphers how protein bioactivity depends on protein loading/release for this technology utilizing catalase as a promising antioxidant therapeutic agent. Catalase has been loaded into CaCO3 using two approaches: i) passive - via adsorption (ADS) into pre-formed crystals and ii) active - via co-synthesis (COS) in the pH range 8–10. Crystal morphology, protein secondary structure and enzymatic bioactivity, and protein retention upon washing are assessed. The activity reduction (∼70% for COS and ∼20% for ADS) is caused by both protein exposure to an alkaline medium and protein aggregation induced by Ca2+. The aggregation significantly governs protein release kinetics. Catalase loading into the crystals is pH-independent and van der Waals interactions dominate over the electrostatics, while catalase activity strongly depends on pH. This study implicates the prime role of loading/release mechanism in the preservation of protein bioactivity and guide for the control over the retention of protein bioactivity.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Calcium carbonate; Circular dichroism; Co-synthesis; Encapsulation; Mesoporous

Biodegradation-Resistant Multilayers Coated with Gold Nanoparticles. Toward a Tailor-made Artificial Extracellular Matrix - Prokopovic, Vladimir Z.; Vikulina, Anna S.; Sustr, David; Duschl, Claus; Volodkin, Dmitry (ACS Applied Materials and Interfaces, 2016)
Polymer multicomponent coatings such as multilayers mimic an extracellular matrix (ECM) that attracts significant attention for the use of the multilayers as functional supports for advanced cell culture and tissue engineering. Herein, biodegradation and molecular transport in hyaluronan/polylysine multilayers coated with gold nanoparticles were described. Nanoparticle coating acts as a semipermeable barrier that governs molecular transport into/from the multilayers and makes them biodegradation-resistant. Model protein lysozyme (mimics of ECM-soluble signals) diffuses into the multilayers as fast- and slow-diffusing populations existing in an equilibrium. Such a composite system may have high potential to be exploited as degradation-resistant drug-delivery platforms suitable for cell-based applications.
CRIS-Team Scopus Importer:2021-06-08
Keywords: cell adhesion; diffusion; enzymatic degradation; fluorescence recovery after photobleaching; hyaluronic acid; layer-by-layer; polylysine; semipermeable

Bio-friendly encapsulation of superoxide dismutase into vaterite CaCO3 crystals. Enzyme activity, release mechanism, and perspectives for ophthalmology - Binevski, Petr V.; Balabushevich, Nadezhda G.; Uvarova, Viktoria I.; Vikulina, Anna S.; Volodkin, Dmitry (Colloids and Surfaces B: Biointerfaces, 2019)
Mesoporous vaterite CaCO3 crystals are nowadays one of the most popular vectors for loading of fragile biomolecules like proteins due to biocompatibility, high loading capacity, cost effective and simple loading procedures. However, recent studies reported the reduction of bioactivity for protein encapsulation into the crystals in water due to rather high alkaline pH of about 10.3 caused by the crystal hydrolysis. In this study we have investigated how to retain the bioactivity and control the release rate of the enzyme superoxide dismutase (SOD) loaded into the crystals via co-synthesis. SOD is widely used as an antioxidant in ophthalmology and its formulations with high protein content and activity as well as opportunities for a sustained release are highly desirable. Here we demonstrate that SOD co-synthesis can be done at pH 8.5 in a buffer without affecting crystal morphology. The synthesis in the buffer allows reaching the high loading efficiency of 93%, high SOD content (24 versus 15 w/w % for the synthesis in water), and order of magnitude higher activity compared to the synthesis in water. The enormous SOD concentration into crystals of 10−2 M is caused by the entrapment of SOD aggregates into the crystal pores. The SOD released from crystals at physiologically relevant ionic strength fully retains its bioactivity. As found by fitting the release profiles using zero-order and Baker-Lonsdale models, the SOD release mechanism is governed by both the SOD aggregate dissolution and by the diffusion of SOD molecules thorough the crystal pores. The latest process contributes more in case of the co-synthesis in the buffer because at higher pH (co-synthesis in water) the unfolded SOD molecules aggregate stronger. The release is bi-modal with a burst (ca 30%) followed by a sustained release and a complete release due to the recrystallization of vaterite crystals to non-porous calcite crystals. The mechanism of SOD loading into and release from the crystals as well as perspectives for the use of the crystals for SOD delivery in ophthalmology are discussed. We believe that together with a fundamental understanding of the vaterite-based protein encapsulation and protein release, this study will help to establish a power platform for a mild and effective encapsulation of fragile biomolecules like proteins at bio-friendly conditions.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Calcite; Ocular drug delivery; Protein; Recrystallization; Sustained release

Biopolymer-based microgels as the carriers for surface functionalization - Campbell, Jack; Rothfelder, Richard; Wittmann, Alexander; Schmidt, Michael; Volodkin, Dmitry; Vikulina, Anna (16th European Symposium on Controlled Drug Delivery, 2022)

CaCO3 crystals as versatile carriers for controlled delivery of antimicrobials - Ferreira, Ana M.; Vikulina, Anna S.; Volodkin, Dmitry (Journal of Controlled Release, 2020)
CaCO3 crystals have been known for a long time as naturally derived and simply fabricated nano(micro)-sized materials able to effectively host and release various molecules. This review summarises the use of CaCO3 crystals as versatile carriers to host, protect and release antimicrobials, offering a strong tool to tackle antimicrobial resistance, a serious global health problem. The main methods for the synthesis of CaCO3 crystals with different properties, as well as the approaches for the loading and release of antimicrobials are presented. Finally, prospects to utilize the crystals in order to improve the therapeutic outcome and combat antimicrobial resistance are highlighted. Ultimately, this review intends to provide an in-depth overview of the application of CaCO3 crystals for the smart and controlled delivery of antimicrobial agents and aims at identifying the advantages and drawbacks as well as guiding future works, research directions and industrial applications.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Antimicrobial resistance; Aragonite; Calcite; Calcium carbonate; Drug delivery carriers; Vaterite

Comparative Characterization of Iron and Silver Nanoparticles: Extract-Stabilized and Classical Synthesis Methods - Akhatova, Farida; Konnova, Svetlana; Kryuchkova, Marina; Batasheva, Svetlana; Mazurova, Kristina; Vikulina, Anna; Volodkin, Dmitry; Rozhina, Elvira (International Journal of Molecular Sciences, 2023)
Synthesis of silver nanoparticles using extracts from plants is an advantageous technological alternative to the traditional colloidal synthesis due to its simplicity, low cost, and the inclusion of environmentally friendly processes to obtain a new generation of antimicrobial compounds. The work describes the production of silver and iron nanoparticles using sphagnum extract as well as traditional synthesis. Dynamic light scattering (DLS) and laser doppler velocimetry methods, UV-visible spectroscopy, transmission electron microscopy (TEM) combined with energy dispersive X-ray spectroscopy (EDS), atomic force microscopy (AFM), dark-field hyperspectral microscopy, and Fourier-transform infrared spectroscopy (FT-IR) were used to study the structure and properties of synthesized nanoparticles. Our studies demonstrated a high antibacterial activity of the obtained nanoparticles, including the formation of biofilms. Nanoparticles synthesized using sphagnum moss extracts likely have high potential for further research.
CRIS-Team Scopus Importer:2023-06-30
Keywords: extract-stabilized nanoparticles; iron nanoparticles (FeNPs); silver nanoparticles (AgNP); Sphagnum fallax

Comparative cytotoxicity of kaolinite, halloysite, multiwalled carbon nanotubes and graphene oxide - Rozhina, Elvira; Batasheva, Svetlana; Miftakhova, Regina; Yan, Xuehai; Vikulina, Anna S.; Volodkin, Dmitry; Fakhrullin, Rawil (Applied Clay Science, 2021)
This study aimed at comparative examining of the interactions between conventionally used clay and carbon nanomaterials and human lung adenocarcinoma cells (A549 cells). The following platy and tubular nanomaterials were tested: carbon nanoparticles, i.e. multi-walled carbon nanotubes (MWCNTs) and graphene oxide nanosheets (GO) as well as nanoclays, i.e. halloysite nanotubes (HNTs) and kaolinite nanosheets (Kaol). Nanoparticle physicochemical properties and their internalization into cells were examined using dynamic light scattering as well as atomic force, 3D laser scanning confocal and darkfield hyperspectral microscopies. Biological aspects of the nanomaterial-cell interaction included assessment of cellular toxicity, DNA damage, metabolic activity, and physical parameters of the cells. Regardless of a shape, carbon nanomaterials demonstrated cell surface adsorption, but negligible penetration into cells compared to nanoclays. However, carbon nanomaterials were found to be the most toxic for cells as probed by the MTS assay. They also turned out to be the most genotoxic for cells compared to nanoclays as revealed by the DNA-Comet assay. GO significantly increased the fraction of apoptotic cells and was the most cytotoxic and genotoxic nanomaterial. Comparison of flow cytometry and MTS data indicated that a cytotoxic effect of MWCNTs was not associated with increased cell death, but was rather due to a decrease in cell metabolic activity and/or proliferation. Finally, no significant effect of the shape of the tested nanomaterials on their internalization and cytotoxicity was revealed.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Cytotoxicity; Genotoxicity; Graphene oxide; Halloysite; Kaolinite; Multiwalled carbon nanotubes

Controlling the Vaterite CaCO3 Crystal Pores. Design of Tailor-Made Polymer Based Microcapsules by Hard Templating - Feoktistova, Natalia; Rose, Juergen; Prokopovic, Vladimir Z.; Vikulina, Anna S.; Skirtach, Andre; Volodkin, Dmitry (Langmuir, 2016)
The spherical vaterite CaCO3 microcrystals are nowadays widely used as sacrificial templates for fabrication of various microcarriers made of biopolymers (e.g., proteins, nucleic acids, enzymes) due to porous structure and mild template elimination conditions. Here, we demonstrated for the first time that polymer microcarriers with tuned internal nanoarchitecture can be designed by employing the CaCO3 crystals of controlled porosity. The layer-by-layer deposition has been utilized to assemble shell-like (hollow) and matrix-like (filled) polymer capsules due to restricted and free polymer diffusion through the crystal pores, respectively. The crystal pore size in the range of few tens of nanometers can be adjusted without any additives by variation of the crystal preparation temperature in the range 7-45 °C. The temperature-mediated growth mechanism is explained by the Ostwald ripening of nanocrystallites forming the crystal secondary structure. Various techniques including SEM, AFM, CLSM, Raman microscopy, nitrogen adsorption-desorption, and XRD have been employed for crystal and microcapsule analysis. A three-dimensional model is introduced to describe the crystal internal structure and predict the pore cutoff and available surface for the pore diffusing molecules. Inherent biocompatibility of CaCO3 and a possibility to scale the porosity in the size range of typical biomacromolecules make the CaCO3 crystals extremely attractive tools for template assisted designing tailor-made biopolymer-based architectures in 2D to 3D targeted at drug delivery and other bioapplications.
CRIS-Team Scopus Importer:2021-06-08

Cooling-Triggered Release from Mesoporous Poly(N-isopropylacrylamide) Microgels at Physiological Conditions - Vikulina, Anna S.; Feoktistova, Natalia A.; Balabushevich, Nadezhda G.; Von Klitzing, Regine; Volodkin, Dmitry (ACS Applied Materials and Interfaces, 2020)
Poly(N-isopropylacrylamide) (pNIPAM) hydrogels have broad potential applications as drug delivery vehicles because of their thermoresponsive behavior. pNIPAM loading/release performances are directly affected by the gel network structure. Therefore, there is a need with the approaches for accurate design of 3D pNIPAM assemblies with the structure ordered at the nanoscale. This study demonstrates size-selective spontaneous loading of macromolecules (dextrans 10-500 kDa) into pNIPAM microgels by microgel heating from 22 to 35 °C (microgels collapse and trap dextrans) followed by the dextran release upon further cooling down to 22 °C (microgels swell back). This temperature-mediated behavior is fully reversible. The structure of pNIPAM microgels was tailored via hard templating and cross-linking of the hydrogel using sacrificial mesoporous cores of vaterite CaCO3 microcrystals. In addition, the fabrication of hollow thermoresponsive pNIPAM microshells has been demonstrated, utilizing vaterite microcrystals that had narrower pores. The proposed approach for heating-triggered encapsulation and cooling-triggered release into/from pNIPAM microgels may pave the ways for applications of pNIPAM hydrogels for skin and transdermal cooling-responsive drug delivery in the future.
CRIS-Team Scopus Importer:2021-06-08
Keywords: calcium carbonate; hard templating; poly(N-isopropylacrylamide); temperature-triggered release; vaterite

Deciphering of mitochondrial cardiolipin oxidative signaling in cerebral ischemia-reperfusion - Ji, Jing; Baart, Sophie; Vikulina, Anna S.; Clark, Robert S. B.; Anthonymuthu, Tamil S.; Tyurin, Vladimir A.; Du, Lina; St Croix, Claudette M.; Tyurina, Yulia Y.; Lewis, Jesse; Skoda, Erin M.; Kline, Anthony E.; et al. (Journal of Cerebral Blood Flow and Metabolism, 2015)
It is believed that biosynthesis of lipid mediators in the central nervous system after cerebral ischemia-reperfusion starts with phospholipid hydrolysis by calcium-dependent phospholipases and is followed by oxygenation of released fatty acids (FAs). Here, we report an alternative pathway whereby cereberal ischemia-reperfusion triggered oxygenation of a mitochondria-specific phospholipid, cardiolipin (CL), is followed by its hydrolysis to yield monolyso-CLs and oxygenated derivatives of fatty (linoleic) acids. We used a model of global cerebral ischemia-reperfusion characterized by 9 minutes of asphyxia leading to asystole followed by cardiopulmonary resuscitation in postnatal day 17 rats. Global ischemia and cardiopulmonary resuscitation resulted in: (1) selective oxidation and hydrolysis of CLs, (2) accumulation of lyso-CLs and oxygenated free FAs, (3) activation of caspase 3/7 in the brain, and (4) motor and cognitive dysfunction. On the basis of these findings, we used a mitochondria targeted nitroxide electron scavenger, which prevented CL oxidation and subsequent hydrolysis, attenuated caspase activation, and improved neurocognitive outcome when administered after cardiac arrest. These data show that calcium-independent CL oxidation and subsequent hydrolysis represent a previously unidentified pathogenic mechanism of brain injury incurred by ischemia-reperfusion and a clinically relevant therapeutic target.
CRIS-Team Scopus Importer:2021-06-08
Keywords: cardiac arrest; cardiopulmonary resuscitation; heart arrest; XJB-5-131

Dextran and Its Derivatives: Biopolymer Additives for the Modulation of Vaterite CaCO3 Crystal Morphology and Adhesion to Cells - Campbell, Jack; Ferreira, Ana M.; Bowker, Laura; Hunt, John; Volodkin, Dmitry; Vikulina, Anna (Advanced Materials Interfaces, 2022)
Nowadays, a great demand for the development of novel drug delivery systems with high potential for bench-to-market transition attracts scientific attention toward materials that are already approved for biomedical use. Here, controlled fabrication of hybrid organic inorganic mesoporous crystals is realized in physiologically relevant conditions by co-synthesis of vaterite CaCO3 in the presence of dextran (DEX) or its functional derivatives. The effects of DEX molecular weight and chemical structure on morphology, porosity, and stability of the hybrids are investigated. Molecular weight of DEX does not affect the crystal growth but leads to the partial blocking of crystal pores. Co-synthesis of DEX functionalized with either carboxymethyl (CM) or diethylaminoethyl (DEAE) groups drastically increased crystal porosity without influencing crystal size. pH-dependent vaterite-to-calcite recrystallization is significantly suppressed by inclusion of carboxymethyl-dextran (CM-DEX), making vaterite crystals stable in acidic medium, whereas the incorporation of diethylaminoethyl-dextran (DEAE-DEX) has no effect. The hybrids prepared with charged DEX derivatives possess stronger adhesion to normal human dermal fibroblasts: three times higher crystal adherence compared to pristine crystals. These results provide fundamental physical–chemical insights into the crystallization of DEX/vaterite hybrids and are discussed in view of the potential of these functional delivery carriers for biomedical and other applications.
CRIS-Team Scopus Importer:2022-10-07
Keywords: biomineralization; co-synthesis; drug delivery; mesoporous; recrystallization

Editorial for the special issue on self-assembly of polymers - Vikulina, Anna S.; Volodkin, Dmitry (Micromachines, 2019)
CRIS-Team Scopus Importer:2021-06-08

Hierarchy of hybrid materials. Part-II: The place of organics-on-inorganics in it, their composition and applications - Song, Junnan; Vikulina, Anna; Parakhonskiy, Bogdan V.; Skirtach, Andre G. (Frontiers in Chemistry, 2023)
Hybrid materials or hybrids incorporating organic and inorganic constituents are emerging as a very potent and promising class of materials due to the diverse but complementary nature of their properties. This complementarity leads to a perfect synergy of properties of the desired materials and products as well as to an extensive range of their application areas. Recently, we have overviewed and classified hybrid materials describing inorganics-in-organics in Part-I (Saveleva, et al., Front. Chem., 2019, 7, 179). Here, we extend that work in Part-II describing organics–on-inorganics, i.e., inorganic materials modified by organic moieties, their structure and functionalities. Inorganic constituents comprise of colloids/nanoparticles and flat surfaces/matrices comprise of metallic (noble metal, metal oxide, metal-organic framework, magnetic nanoparticles, alloy) and non-metallic (minerals, clays, carbons, and ceramics) materials; while organic additives can include molecules (polymers, fluorescence dyes, surfactants), biomolecules (proteins, carbohydtrates, antibodies and nucleic acids) and even higher-level organisms such as cells, bacteria, and microorganisms. Similarly to what was described in Part-I, we look at similar and dissimilar properties of organic-inorganic materials summarizing those bringing complementarity and composition. A broad range of applications of these hybrid materials is also presented whose development is spurred by engaging different scientific research communities.
CRIS-Team Scopus Importer:2023-02-17
Keywords: colloids; flat surfaces; hybrid materials; inorganics; modifications and applications; nanoparticles; organics

How similar is the antibacterial activity of silver nanoparticles coated with different capping agents? - Ferreira, Ana M.; Vikulina, Anna; Loughlin, Michael; Volodkin, Dmitry (RSC Advances, 2023)
Silver nanoparticles (AgNPs) represent one of the most commercialised metal nanomaterials, with an extensive number of applications that span from antimicrobial products to electronics. Bare AgNPs are very susceptible to aggregation, and capping agents are required for their protection and stabilisation. The capping agents can endow new characteristics which can either improve or deteriorate AgNPs (bio)activity. In the present work, five different capping agents were studied as stabilizing agents for AgNPs: trisodium citrate (citrate), polyvinylpyrrolidone (PVP), dextran (Dex), diethylaminoethyl-dextran (Dex(DEAE)) and carboxymethyl-dextran (Dex(CM)). The properties of the AgNPs were studied using a set of methods, including transmission electron microscopy, X-ray diffraction, thermogravimetric analysis and ultraviolet-visible and infrared spectroscopy. Coated and bare AgNPs were also tested against Escherichia coli, methicillin-resistance Staphylococcus aureus and Pseudomonas aeruginosa to analyse their capacity to suppress bacterial growth and eradicate biofilms of clinically relevant bacteria. The results showed that all the capping agents endow long-term stability for the AgNPs in water; however, when the AgNPs are in bacterial culture media, their stability is highly dependent on the capping agent properties due to the presence of electrolytes and charged macromolecules such as proteins. The results also showed that the capping agents have a substantial impact on the antibacterial activity of the AgNPs. The AgNPs coated with the Dex and Dex(CM) were the most effective against the three strains, due to their better stability which resulted in the release of more silver ions, better interactions with the bacteria and diffusion into the biofilms. It is hypothesized that the antibacterial activity of capped AgNPs is governed by a balance between the AgNPs stability and their ability to release silver ions. Strong adsorption of capping agents like PVP on the AgNPs endows higher colloidal stability in culture media; however, it can decrease the rate of Ag+ release from the AgNPs and reduce the antibacterial performance. Overall, this work presents a comparative study between different capping agents on the properties and antibacterial activity of AgNPs, highlighting the importance of the capping agent in their stability and bioactivity.
CRIS-Team WoS Importer:2023-04-28

Hybrid CaCO3-mucin crystals: Effective approach for loading and controlled release of cationic drugs - Balabushevich, Nadezhda G.; Kovalenko, Ekaterina A.; Le-Deygen, Irina M.; Filatova, Lyubov Y.; Volodkin, Dmitry; Vikulina, Anna S. (Materials & Design, 2019)
Vaterite CaCO3 crystals are actively used as a biocompatible and degradable matrix for encapsulation of fragile biomacromolecules. However, the incorporation of small cationic drugs into the crystals remains awkward due to a poor binding of these drugs to the crystal surface and scarce retention inside the crystal pores. Herein, we achieve efficient drug loading and control over drug release performance via utilisation of hybrid CaCO3 crystals impregnated with mucin. The co-loading of mucin and anticancer drug doxorubicin (DOX) into CaCO3 crystals enhanced drug content in the crystals by ca 12 times giving DOX concentration of 1.3 mg g−1 CaCO3. Retention of DOX inside hybrid crystals is governed by strong electrostatic attraction to mucin matrix and significant narrowing of the crystal pores in the presence of mucin. At physiologically relevant conditions, DOX release kinetics strongly depends on the recrystallization of the porous vaterite to non-porous calcite that is regulated by mucin concentration. We believe that this study will help to design novel effective drug delivery systems able to load high amounts of drugs at mild conditions for sustained and controlled release of the drugs. This is indispensable for mucosal delivery where mucin produced by epithelial tissues is a main component.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Aprotinin; Co-synthesis; Doxorubicin; Mucosal delivery; Prolonged release; Vaterite

Hybrids of Polymer Multilayers, Lipids, and Nanoparticles: Mimicking the Cellular Microenvironment - Vikulina, Anna S.; Skirtach, A. G.; Volodkin, Dmitry (Langmuir, 2019)
Here we address research directions and trends developed following novel concepts in 2D/3D self-assembled polymer structures established in the department led by Helmuth Möhwald. These functional structures made of hybrids of polymer multilayers, lipids, and nanoparticles stimulated research in the design of the cellular microenvironment. The composition of the extracellular matrix (ECM) and dynamics of biofactor presentation in the ECM can be recapitulated by the hybrids. Proteins serve as models for protein-based biofactors such as growth factors, cytokines, hormones, and so forth. A fundamental understanding of complex intermolecular interactions and approaches developed for the externally IR-light-triggered release offers a powerful tool for controlling the biofactor presentation. Pure protein beads made via a mild templating on vaterite CaCO3 crystals can mimic cellular organelles in terms of the compartmentalization of active proteins. We believe that an integration of the approaches developed and described here offers a strong tool for engineering and mimicking both extra- and intracellular microenvironments.
CRIS-Team Scopus Importer:2021-06-08

Immobilization of Antioxidant Enzyme Catalase on Porous Hybrid Microparticles of Vaterite with Mucin - Balabushevich, Nadezhda G.; Kovalenko, Ekaterina A.; Maltseva, Liliya N.; Filatova, Lyubov Yu; Moysenovich, Anastasia M.; Mikhalchik, Elena; Volodkin, Dmitry; Vikulina, Anna (Advanced Engineering Materials, 2022)
Catalase is one of the crucial antioxidant enzymes with diverse applications in textile, food industries, wastewater treatment, cosmetics, and pharmaceutics, which, however, is highly sensitive to environmental challenges. Resisting the loss of activity and prolongation of formulation storage can be achieved via the catalase entrapment into insoluble carriers. Affordable and degradable vaterite is proposed as amicable material for catalase immobilization. To improve the carrier properties of the vaterite, it was co-precipitated with mucin from the pig's stomach producing ca 5 μm hybrid mucin/vaterite microparticles. Catalase is impregnated into the crystals by means of adsorption without chemical modifications. The presence of mucin matrix partially hinders catalase penetration into the crystals and reduces the adsorption capacity (for 0.1 mg mL−1 catalase, ca 2.3 vs ca 1.5 mg g−1 for pristine and hybrid microparticles, respectively) but significantly promotes the protection of antioxidant activity upon storage and under the action of temperature, organic solvent (acetonitrile), and proteolytic enzyme (trypsin). Hybrid microcrystals are pH-sensitive and better retain the enzyme at pH 3–5 due to catalase-mucin complexation. Immobilized catalase can be used for 5–6 consecutive cycles until it loses catalytic activity. Altogether, these findings indicate promises of hybrid mucin/vaterite microparticles for immobilization of antioxidant enzymes.
CRIS-Team Scopus Importer:2022-05-13
Keywords: adsorption; antioxidant enzyme; catalase; drug carrier; mucosal delivery

Internal structure of matrix-type multilayer capsules templated on porous vaterite CaCO3 crystals as probed by staining with a fluorescence dye - Jeannot, Lucas; Bell, Michael; Ashwell, Ryan; Volodkin, Dmitry; Vikulina, Anna S. (Micromachines, 2018)
Multilayer capsules templated on decomposable vaterite CaCO3 crystals are widely used as vehicles for drug delivery. The capsule represents typically not a hollow but matrix-like structure due to polymer diffusion into the porous crystals during multilayer deposition. The capsule formation mechanism is not well-studied but its understanding is crucial to tune capsule structure for a proper drug release performance. This study proposes new approach to noninvasively probe and adjust internal capsule structure. Polymer capsules made of poly(styrene-sulfonate) (PSS) and poly(diallyldimethylammonium chloride) (PDAD) have been stained with fluorescence dye rhodamine 6G. Physical-chemical aspects of intermolecular interactions required to validate the approach and adjust capsule structure are addressed. The capsules consist of a defined shell (typically 0.5-2 μm) and an internal matrix of PSS-PDAD complex (typically 10-40% of a total capsule volume). An increase of ionic strength and polymer deposition time leads to the thickening of the capsule shell and formation of a denser internal matrix, respectively. This is explained by effects of a polymer conformation and limitations in polymer diffusion through the crystal pores. We believe that the design of the capsules with desired internal structure will allow achieving effective encapsulation and controlled/programmed release of bioactives for advanced drug delivery applications.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Calcium carbonate; Fluorescence; Layer-by-layer; Mesoporous; Self-assembly

Inter-protein interactions govern protein loading into porous vaterite CaCO3crystals - Feoktistova, Natalia A.; Balabushevich, Nadezhda G.; Skirtach, Andre G.; Volodkin, Dmitry; Vikulina, Anna S. (Physical Chemistry Chemical Physics, 2020)
The fast development of protein therapeutics has resulted in a high demand for advanced delivery carriers that can effectively host therapeutic proteins, preserve their bioactivity and release them on demand. Accordingly, vaterite CaCO3 crystals have attracted special attention as sacrificial templates for protein encapsulation in micro- and nanoparticles (capsules and beads, respectively) under mild biofriendly conditions. This study aimed to better understand the mechanism of protein loading into crystals as a primary step for protein encapsulation. The loading of three therapeutic proteins (250 kDa catalase, 5.8 kDa insulin, and 6.5 kDa aprotinin) was investigated for crystals with different porosities. However, unexpectedly, the protein loading capacity was not consistent with the protein molecular weight. It solely depends on the inter-protein interactions in the bulk solution in the presence of crystals and that inside the crystals. The smallest protein aprotinin aggregates in the bulk (its aggregate size is about 100 nm), which prohibits its loading into the crystals. Insulin forms hexamers in the bulk, which can diffuse into the crystal pores but tend to aggregate inside the pores, suppressing protein diffusion inward. Catalase, the largest protein tested, does not form any aggregates in the bulk and diffuses freely into the crystals; however, its diffusion into small pores is sterically restricted. These findings are essential for the encapsulation of protein therapeutics by means of templating based on CaCO3 crystals and for the engineering of protein-containing microparticles having desired architectures.
CRIS-Team Scopus Importer:2021-06-08

Layer-by-layer assemblies of biopolymers: Build-up, mechanical stability and molecular dynamics - Campbell, Jack; Vikulina, Anna S. (Polymers, 2020)
Rapid development of versatile layer-by-layer technology has resulted in important breakthroughs in the understanding of the nature of molecular interactions in multilayer assemblies made of polyelectrolytes. Nowadays, polyelectrolyte multilayers (PEM) are considered to be non-equilibrium and highly dynamic structures. High interest in biomedical applications of PEMs has attracted attention to PEMs made of biopolymers. Recent studies suggest that biopolymer dynamics determines the fate and the properties of such PEMs; however, deciphering, predicting and controlling the dynamics of polymers remains a challenge. This review brings together the up-to-date knowledge of the role of molecular dynamics in multilayers assembled from biopolymers. We discuss how molecular dynamics determines the properties of these PEMs from the nano to the macro scale, focusing on its role in PEM formation and non-enzymatic degradation. We summarize the factors allowing the control of molecular dynamics within PEMs, and therefore to tailor polymer multilayers on demand.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Degradation; Diffusion; Film growth; Polyelectrolyte multilayers; Thin films

LC/MS analysis of cardiolipins in substantia nigra and plasma of rotenone-treated rats: Implication for mitochondrial dysfunction in Parkinson's disease - Tyurina, Y. Y.; Polimova, A. M.; Maciel, Elisabete; Tyurin, V. A.; Kapralova, V. I.; Winnica, D. E.; Vikulina, Anna S.; Domingues, M. R. M.; Mccoy, Jennifer L.; Sanders, L. H.; Bayir, H.; Greenamyre, J. T.; et al. (Free Radical Research, 2015)
Exposure to rotenone in vivo results in selective degeneration of dopaminergic neurons and development of neuropathologic features of Parkinson's disease (PD). As rotenone acts as an inhibitor of mitochondrial respiratory complex I, we employed oxidative lipidomics to assess oxidative metabolism of a mitochondria-specific phospholipid, cardiolipin (CL), in substantia nigra (SN) of exposed animals. We found a significant reduction in oxidizable polyunsaturated fatty acid (PUFA)-containing CL molecular species. We further revealed increased contents of mono-oxygenated CL species at late stages of the exposure. Notably, linoleic acid in sn-1 position was the major oxidation substrate yielding its mono-hydroxy- and epoxy-derivatives whereas more readily "oxidizable" fatty acid residues (arachidonic and docosahexaenoic acids) remained non-oxidized. Elevated levels of PUFA CLs were detected in plasma of rats exposed to rotenone. Characterization of oxidatively modified CL molecular species in SN and detection of PUFA-containing CL species in plasma may contribute to better understanding of the PD pathogenesis and lead to the development of new biomarkers of mitochondrial dysfunction associated with this disease.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Cardiolipin; Oxygenated cardiolipin species; Oxygenated linoleic acid; Parkinson's disease

Mesoporous additive-free vaterite CaCO3 crystals of untypical sizes: From submicron to Giant - Vikulina, Anna S.; Webster, Joseph; Voronin, Denis; Ivanov, Evgenii; Fakhrullin, Rawil; Vinokurov, Vladimir; Volodkin, Dmitry (Materials & Design, 2021)
Mesoporous CaCO3 crystals of sizes in the range 3–15 μm have attracted significant scientific attention as fully decomposable biocompatible drug delivery vectors. They are also used as sacrificial templates to produce polymer-based microcarriers (capsules, beads) and polymer scaffolds for tissue engineering at biologically friendly conditions. However, fabrication of CaCO3 crystals with the sizes beyond the conventional range without additives is still a challenge. There is a desperate need of sub-micrometre and sub-millimetre biocompatible and easily decomposable vectors for intracellular delivery and design of tailor-made polymer scaffolds, respectively. In this study, additive-free one-step fabrication of vaterite mesoporous crystals with sizes in the range from submicron (0.72 μm) up to tens of microns (55 μm) sizes is proposed. Crystals are grown by mixing of Ca2+ and CO32− salts in aqueous media. Internal structure and morphology of the crystals have been investigated. Encapsulation of lysozyme by means of co-synthesis shows an enhanced entrapment into submicron crystals. Besides, the approach to grow CaCO3 crystals on the surface of microcellulose ьш is demonstrated opening broad avenues for the development of vaterite coatings technologies.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Adsorption isotherm; Calcium carbonate; Carriers; Decomposable; Drug delivery; Encapsulation

Mobility of lysozyme in poly(L-lysine)/hyaluronic acid multilayer films - Velk, Natalia; Uhlig, Katja; Vikulina, Anna S.; Duschl, Claus; Volodkin, Dmitry (Colloids and Surfaces B: Biointerfaces, 2016)
The spatial and temporal control over presentation of protein-based biomolecules such as growth factors and hormones is crucial for in vitro applications to mimic the complex in vivo environment. We investigated the interaction of a model protein lysozyme (Lys) with poly(L-lysine)/hyaluronic acid (PLL/HA) multilayer films. We focused on Lys diffusion as well as adsorption and retention within the film as a function of the film deposition conditions and post-treatment. Additionally, an effect of Lys concentration on its mobility was probed. A combination of confocal fluorescence microscopy, fluorescence recovery after photobleaching, and microfluidics was employed for this investigation. Our main finding is that adsorption of PLL and HA after protein loading induces acceleration and reduction of Lys mobility, respectively. These results suggest that a charge balance in the film to a high extent governs the protein–film interaction. We believe that control over protein mobility is a key to reach the full potential of the PLL/HA films as reservoirs for biomolecules depending on the application demand.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Diffusion; FRAP; Layer-by-layer; Protein; Release

Mucin adsorption on vaterite CaCO3microcrystals for the prediction of mucoadhesive properties - Balabushevich, Nadezhda G.; Kovalenko, Ekaterina A.; Mikhalchik, Elena; Filatova, Lyubov Y.; Volodkin, Dmitry; Vikulina, Anna S. (Journal of Colloid and Interface Science, 2019)
Porous vaterite CaCO 3 crystals are widely used as containers for drug loading and as sacrificial templates to assemble polymer-based nano- and micro-particles at mild conditions. Special attention is paid nowadays to mucosal delivery where the glycoprotein mucin plays a crucial role as a main component of a mucous. In this work mucoadhesive properties of vaterite crystals have been tested by investigation of mucin binding to the crystals as a function of (i) time, (ii) glycoprotein concentration, (iii) adsorption conditions and (iv) degree of mucin desialization. Mucin adsorption follows Bangham equation indicating that diffusion into crystal pores is the rate-limiting step. Mucin strongly binds to the crystals (ΔG = −35 ± 4 kJ mol −1 ) via electrostatic and hydrophobic interactions forming a gel and thus giving the tremendous mucin mass content in the crystals of up to 16%. Despite strong intermolecular mucin-mucin interactions, pure mucin spheres formed after crystal dissolution are unstable. However, introduction of protamine, actively used for mucosal delivery, makes the spheres stable via additional electrostatic bonding. The results of this work indicate that the vaterite crystals are extremely promising carriers for mucosal drug delivery and for development of test-systems for the analysis of the mucoadhesion.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Desialated mucin; Layer-by-layer; Mucoadhesion; Multilayer; Protamine

Naturally derived nano- And micro-drug delivery vehicles: Halloysite, vaterite and nanocellulose - Vikulina, Anna S.; Voronin, Denis; Fakhrullin, Rawil; Vinokurov, Vladimir; Volodkin, Dmitry (New Journal of Chemistry, 2020)
Recent advances in drug delivery and controlled release had a great impact on bioscience, medicine and tissue engineering. Consequently, a variety of advanced drug delivery vehicles either have already reached the market or are approaching the phase of commercial production. Progressive growth of the drug delivery market has led to the necessity to earnestly concern about economically viable, up-scalable and sustainable technologies for a large-scale production of drug delivery carriers. We have identified three attractive natural sources of drug carriers: aluminosilicate clays, minerals of calcium carbonate, and cellulose. Three classes of drug delivery carriers derived from these natural materials are halloysite nanotubes, vaterite crystals and nanocellulose. These carriers can be produced using "green" technologies from some of the most abundant sources on the Earth and have extremely high potential to meet all criteria applied for the manufacture of modern delivery carriers. We provide an up-to-date snapshot of these drug delivery vehicles towards their use for bioapplications, in particular for drug delivery and tissue engineering. The following research topics are addressed: (i) the availability, sources and methodologies used for production of these drug delivery vehicles, (ii) the drug loading and release mechanisms of these delivery vehicles, (iii) in vitro, in vivo, and clinical studies on these vehicles, and (iv) employment of these vehicles for tissue engineering. Finally, the prospects for vehicles' further development and industrialisation are critically assessed, highlighting most attractive future research directions such as the design of third generation active biomaterials.
CRIS-Team Scopus Importer:2021-06-08

Oxidatively modified phosphatidylserines on the surface of apoptotic cells are essential phagocytic 'eat-me' signals: Cleavage and inhibition of phagocytosis by Lp-PLA 2 - Tyurin, V. A.; Balasubramanian, K.; Winnica, D.; Tyurina, Y. Y.; Vikulina, Anna S.; He, R. R.; Kapralov, A. A.; Macphee, C. H.; Kagan, V. E. (Cell Death and Differentiation, 2014)
Diversified anionic phospholipids, phosphatidylserines (PS), externalized to the surface of apoptotic cells are universal phagocytic signals. However, the role of major PS metabolites, such as peroxidized species of PS (PSox) and lyso-PS, in the clearance of apoptotic cells has not been rigorously evaluated. Here, we demonstrate that H 2O2 was equally effective in inducing apoptosis and externalization of PS in naive HL60 cells and in cells enriched with oxidizable polyunsaturated species of PS (supplemented with linoleic acid (LA)). Despite this, the uptake of LA-supplemented cells by RAW264.7 and THP-1 macrophages was more than an order of magnitude more effective than that of naive cells. A similar stimulation of phagocytosis was observed with LA-enriched HL60 cells and Jurkat cells triggered to apoptosis with staurosporine. This was due to the presence of PSox on the surface of apoptotic LA-supplemented cells (but not of naive cells). This enhanced phagocytosis was dependent on activation of the intrinsic apoptotic pathway, as no stimulation of phagocytosis occurred in LA-enriched cells challenged with Fas antibody. Incubation of apoptotic cells with lipoprotein-associated phospholipase A 2 (Lp-PLA 2), a secreted enzyme with high specificity towards PSox, hydrolyzed peroxidized PS species in LA-supplemented cells resulting in the suppression of phagocytosis to the levels observed for naive cells. This suppression of phagocytosis by Lp-PLA 2 was blocked by a selective inhibitor of Lp-PLA 2, SB-435495. Screening of possible receptor candidates revealed the ability of several PS receptors and bridging proteins to recognize both PS and PSox, albeit with diverse selectivity. We conclude that PSox is an effective phagocytic 'eat-me' signal that participates in the engulfment of cells undergoing intrinsic apoptosis. © 2014 Macmillan Publishers Limited All rights reserved.
CRIS-Team Scopus Importer:2021-06-08
Keywords: apoptosis; inflammation; lipoprotein-associated phospholipase; oxidative stress; oxidized phosphatidylserines; phagocytosis; phosphatidylserines

Pharmaceuticals removal by adsorption with montmorillonite nanoclay - Kryuchkova, Marina; Batasheva, Svetlana; Akhatova, Farida; Babaev, Vasily; Buzyurova, Daina; Vikulina, Anna; Volodkin, Dmitry; Fakhrullin, Rawil; Rozhina, Elvira (International Journal of Molecular Sciences, 2021)
The problem of purifying domestic and hospital wastewater from pharmaceutical compounds is becoming more and more urgent every year, because of the continuous accumulation of chemical pollutants in the environment and the limited availability of freshwater resources. Clay adsorbents have been repeatedly proposed as adsorbents for treatment purposes, but natural clays are hydrophilic and can be inefficient for catching hydrophobic pharmaceuticals. In this paper, a comparison of adsorption properties of pristine montmorillonite (MMT) and montmorillonite modified with stearyl trimethyl ammonium (hydrophobic MMT-STA) towards carbamazepine, ibuprofen, and paracetamol pharmaceuticals was performed. The efficiency of adsorption was investigated under varying solution pH, temperature, contact time, initial concentration of pharmaceuticals, and adsorbate/adsorbent mass ratio. MMT-STA was better than pristine MMT at removing all the pharmaceuticals studied. The adsorption capacity of hydrophobic montmorillonite to pharmaceuticals decreased in the following order: carbamazepine (97%) >ibuprofen (95%) > paracetamol (63–67%). Adsorption isotherms were best described by Freundlich model. Within the pharmaceutical concentration range of 10–50 µg/mL, the most optimal mass ratio of adsorbates to adsorbents was 1:300, pH 6, and a temperature of 25◦ C. Thus, MMT-STA could be used as an efficient adsorbent for deconta×ating water of carbamazepine, ibuprofen, and paracetamol.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Adsorption; Clay minerals; Pharmaceuticals; Treatment effectiveness

Porous alginate scaffolds assembled using vaterite CaCO3 crystals - Sergeeva, Alena; Vikulina, Anna S.; Volodkin, Dmitry (Micromachines, 2019)
Formulation of multifunctional biopolymer-based scaffolds is one of the major focuses in modern tissue engineering and regenerative medicine. Besides proper mechanical/chemical properties, an ideal scaffold should: (i) possess a well-tuned porous internal structure for cell seeding/growth and (ii) host bioactive molecules to be protected against biodegradation and presented to cells when required. Alginate hydrogels were extensively developed to serve as scaffolds, and recent advances in the hydrogel formulation demonstrate their applicability as "ideal" soft scaffolds. This review focuses on advanced porous alginate scaffolds (PAS) fabricated using hard templating on vaterite CaCO3 crystals. These novel tailor-made soft structures can be prepared at physiologically relevant conditions offering a high level of control over their internal structure and high performance for loading/release of bioactive macromolecules. The novel approach to assemble PAS is compared with traditional methods used for fabrication of porous alginate hydrogels. Finally, future perspectives and applications of PAS for advanced cell culture, tissue engineering, and drug testing are discussed.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Calcium alginate; Calcium carbonate; Cell culture; Drug delivery; Encapsulation; Polymer scaffold; Porous hydrogel

Porous Alginate Scaffolds Designed by Calcium Carbonate Leaching Technique - Wulf, Alena; Mendgaziev, Rais; Fakhrullin, Rawil; Vinokurov, Vladimir; Volodkin, Dmitry; Vikulina, Anna (Advanced Functional Materials, 2021)
One of the main challenges in modern tissue engineering is to design biocompatible scaffolds with finely tuned porous architecture and capacity to load bioactive molecules that guide the growth and differentiation of the cells during tissue reconstruction. This work proposes a strategy to design porous alginate scaffolds (PAS) with well-tuned architecture by leaching of sacrificial vaterite CaCO3 microspheres packed in alginate. Pore size and interconnectivity depend on CaCO3 sphere dimensions and packing as well as alginate concentration. Varying of these parameters, almost hundred percent pore interconnectivity (or, by contrast, a zero pore interconnectivity) can be achieved. Junctions between interconnected pores are about 50-70% of the pore dimensions that provides molecular transport through the PASs potentially ensuring diffusion of nutrition, oxygen and metabolic products when cell seeding. An opportunity to fabricate a multifunctional scaffold is demonstrated by encapsulation of desired macromolecules into the individual pores of a scaffold (is illustrated by dextran loading). Mechanical properties of PASs are found typical for soft and hydrated structures (Young's modulus of 19 +/- 15 kPa) which is appropriate for cell seeding. The three cell lines (HeLa, HEK293, and L929) are cultured on different alginate scaffolds to examine cell viability and adhesiveness.
CRIS-Team WoS Importer:2021-12-24

Self-assembled mucin-containing microcarriers via hard templating on CaCO3 crystals - Balabushevich, Nadezhda G.; Sholina, Ekaterina A.; Mikhalchik, Elena V.; Filatova, Lyubov Y.; Vikulina, Anna S.; Volodkin, Dmitry (Micromachines, 2018)
Porous vaterite crystals of CaCO3 are extensively used for the fabrication of self-assembled polymer-based microparticles (capsules, beads, etc.) utilized for drug delivery and controlled release. The nature of the polymer used plays a crucial role and discovery of new perspective biopolymers is essential to assemble microparticles with desired characteristics, such as biocompatibility, drug loading efficiency/capacity, release rate, and stability. Glycoprotein mucin is tested here as a good candidate to assemble the microparticles because of high charge due to sialic acids, mucoadhesive properties, and a tendency to self-assemble, forming gels. Mucin loading into the crystals via co-synthesis is twice as effective as via adsorption into preformed crystals. Desialylated mucin has weaker binding to the crystals most probably due to electrostatic interactions between sialic acids and calcium ions on the crystal surface. Improved loading of low-molecular-weight inhibitor aprotinin into the mucin-containing crystals is demonstrated. Multilayer capsules (mucin/protamine)3 have been made by the layer-by-layer self-assembly. Interestingly, the deposition of single mucin layers (mucin/water)3 has also been proven, however, the capsules were unstable, most probably due to additional (to hydrogen bonding) electrostatic interactions in the case of the two polymers used. Finally, approaches to load biologically-active compounds (BACs) into the mucin-containing microparticles are discussed.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Adsorption; Aprotinin; CaCO; Co-synthesis; Layer-by-layer; Mucin; Protamine

Structure of the complex of cytochrome c with cardiolipin in non-polar environment - Vladimirov, G. K.; Vikulina, Anna S.; Volodkin, Dmitry; Vladimirov, Yu A. A. (Chemistry and physics of lipids, 2018)
The complex of mitochondrial protein cytochrome c (CytC) with anionic phospholipid cardiolipin (CL) plays a crucial role in the initiation of apoptosis by catalyzing lipid peroxidation in mitochondrial membranes. In our previous papers, we found that CytC and CL mixed in millimolar concentrations form a sediment showing microcrystals composed of nanospheres (Cyt-CL) of 11–12 and 8 nm in diameter. The hypothesis was proposed that Cyt-CL, having hydrophobic shell, may appear inside the membrane lipid bilayer in mitochondria and peroxidase membrane phospholipids so initiating the apoptotic cascade. In this work, Cyt-CL complex dissolved in chloroform or hexane was investigated as a model of the complex in mitochondrial membranes. We used dynamic light scattering method to measure the size of the particles. The analysis of particles size distribution of Cyt-CL in chloroform allows to reveal three dominant diameters of 12.1 ± 1.4, 7.8 ± 1.0, and 4.7 ± 0.7 nm. The first two values are closed to those, earlier obtained with small-angle X-ray scattering method in Cyt-CL microcrystals, 11.1 ± 1.0 and 8.0 ± 0.7 nm. CL extracted in chloroform-methanol forms a real solution of particles with diameter of 0.7 ± 0.1 nm. In methanol-water phase, CL and CL + CytC mixture form particles of 83.7 ± 9.8 and 71.3 ± 11.6 nm, respectively. Apparently, cardiolipin in 50% methanol forms single-layer liposomes regardless of the presence of CytC in the medium. Partial unfolding of CytC in the complex was evidenced by (a) appearance of fluorescence of tyrosine and tryptophan residues and (b) disappearance of the absorption band at 699 nm due to breakdown of heme iron – methionine bond > F⋯S(Met80). In hydrophobic solvent Cyt-CL exhibited quasi-lipoperoxidase and lipoxygenase activity as was shown in kinetic measurements of chemiluminescence enhanced by coumarin C-525, a selective sensitizer of chemiluminescence, associated with reactions of lipid peroxyl radicals. Our data in this model system do not contradict the hypothesis (Vladimirov, Y.A. et al. Biochemistry (Mosc) 78, 1086–1097) that nanospheres of Cyt-CL complex, embedded into the lipid phase of mitochondrial membrane, catalyze lipid peroxidation, thereby initiating apoptosis.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Cardiolipin; Chemiluminescence; Cytochrome c; Dynamic light scattering

Surface Modification with Particles Coated or Made of Polymer Multilayers - Kotoulas, Konstantinos T. T.; Campbell, Jack; Skirtach, Andre G. G.; Volodkin, Dmitry; Vikulina, Anna (Pharmaceutics, 2022)
The coating of particles or decomposable cores with polyelectrolytes via Layer-by-Layer (LbL) assembly creates free-standing LbL-coated functional particles. Due to the numerous functions that their polymers can bestow, the particles are preferentially selected for a plethora of applications, including, but not limited to coatings, cargo-carriers, drug delivery vehicles and fabric enhancements. The number of publications discussing the fabrication and usage of LbL-assembled particles has consistently increased over the last vicennial. However, past literature fails to either mention or expand upon how these LbL-assembled particles immobilize on to a solid surface. This review evaluates examples of LbL-assembled particles that have been immobilized on to solid surfaces. To aid in the formulation of a mechanism for immobilization, this review examines which forces and factors influence immobilization, and how the latter can be confirmed. The predominant forces in the immobilization of the particles studied here are the Coulombic, capillary, and adhesive forces; hydrogen bonding as well as van der Waal's and hydrophobic interactions are also considered. These are heavily dependent on the factors that influenced immobilization, such as the particle morphology and surface charge. The shape of the LbL particle is related to the particle core, whereas the charge was dependant on the outermost polyelectrolyte in the multilayer coating. The polyelectrolytes also determine the type of bonding that a particle can form with a solid surface. These can be via either physical (non-covalent) or chemical (covalent) bonds; the latter enforcing a stronger immobilization. This review proposes a fundamental theory for immobilization pathways and can be used to support future research in the field of surface patterning and for the general modification of solid surfaces with polymer-based nano- and micro-sized polymer structures.
CRIS-Team WoS Importer:2023-02-03

Temperature effect on the build-up of exponentially growing polyelectrolyte multilayers. An exponential-to-linear transition point - Vikulina, Anna S.; Anissimov, Yuri G.; Singh, Prateek; Prokopovic, Vladimir Z.; Uhlig, Katja; Jaeger, Magnus S.; Von Klitzing, Regine; Duschl, Claus; Volodkin, Dmitry (Physical Chemistry Chemical Physics, 2016)
In this study, the effect of temperature on the build-up of exponentially growing polyelectrolyte multilayer films was investigated. It aims at understanding the multilayer growth mechanism as crucially important for the fabrication of tailor-made multilayer films. Model poly(l-lysine)/hyaluronic acid (PLL/HA) multilayers were assembled in the temperature range of 25-85 °C by layer-by-layer deposition using a dipping method. The film growth switches from the exponential to the linear regime at the transition point as a result of limited polymer diffusion into the film. With the increase of the build-up temperature the film growth rate is enhanced in both regimes; the position of the transition point shifts to a higher number of deposition steps confirming the diffusion-mediated growth mechanism. Not only the faster polymer diffusion into the film but also more porous/permeable film structure are responsible for faster film growth at higher preparation temperature. The latter mechanism is assumed from analysis of the film growth rate upon switching of the preparation temperature during the film growth. Interestingly, the as-prepared films are equilibrated and remain intact (no swelling or shrinking) during temperature variation in the range of 25-45 °C. The average activation energy for complexation between PLL and HA in the multilayers calculated from the Arrhenius plot has been found to be about 0.3 kJ mol-1 for monomers of PLL. Finally, the following processes known to be dependent on temperature are discussed with respect to the multilayer growth: (i) polymer diffusion, (ii) polymer conformational changes, and (iii) inter-polymer interactions.
CRIS-Team Scopus Importer:2021-06-08

Temperature-induced molecular transport through polymer multilayers coated with PNIPAM microgels - Vikulina, Anna S.; Aleed, S. T.; Paulraj, Thomas; Vladimirov, Yu. A.; Duschl, Claus; Von Klitzing, Regine; Volodkin, Dmitry (Physical Chemistry Chemical Physics, 2015)
Polyelectrolyte multilayers serve as effective reservoirs for bioactive molecules which are stored and released from the multilayers for cellular applications. However, control over the release without significantly affecting the multilayers and biomolecules is still a challenge. On the other hand, externally stimulated release would make the multilayers promising for the development of stimuli-sensitive planar carriers with release performance switched on demand. In this study soft composite films are designed by coating hyaluronic acid/poly-l-lysine (HA/PLL) multilayers with temperature responsive poly(N-isopropylacrylamide) (PNIPAM) microgels. Microgels are flattened and immersed into the multilayers to maximize the number of contacts with the surrounding polyelectrolytes (HA and PLL). The microgel coating serves as an efficient switchable barrier for the PLL transport into the multilayers. PLL diffusion into the film is significantly hindered at room temperature but is dramatically enhanced at 40 °C above the volume phase transition temperature (VPTT) of PNIPAM at 32 °C associated with microgel shrinkage. Scanning force microscopy micrographs show that the mechanism of volume phase transition on soft surfaces cannot be directly deduced from the processes taking place at solid substrates.
CRIS-Team Scopus Importer:2021-06-08

The mechanism of catalase loading into porous vaterite CaCO3 crystals by co-synthesis - Vikulina, Anna S.; Feoktistova, N. A.; Balabushevich, N. G.; Skirtach, A. G.; Volodkin, D. (Physical Chemistry Chemical Physics, 2018)
Porous vaterite CaCO3 crystals are nowadays extensively used as high-capacity bio-friendly sacrificial templates for the fabrication of such protein-containing nano- and micro-particles as capsules and beads. The first step in the protein encapsulation is performed through loading of the protein molecules into the crystals. Co-synthesis is one of the most useful and simple methods proven to effectively load crystals with proteins; however, the loading mechanism is still unknown. To understand the mechanism, in this study, we focus on the loading of a model protein catalase into the crystals by means of adsorption into pre-formed crystals (ADS) and co-synthesis (COS). Analysis of the physico-chemical characteristics of the protein in solution and during the loading and simulation of the protein packing into the crystals are performed. COS provides more effective loading than ADS giving protein contents in the crystals of 20.3 and 3.5 w/w%, respectively. Extremely high loading for COS providing a local protein concentration of about 550 mg mL-1 is explained by intermolecular protein interactions, i.e. formation of protein aggregates induced by CaCl2 during the co-synthesis. This is supported by a lower equilibrium constant obtained for COS (5 × 105 M-1) than for ADS (23 × 105 M-1), indicating a higher affinity of single protein molecules rather than aggregates to the crystal surface. Fitting the adsorption isotherms by classical adsorption models has shown that the Langmuir and BET models describe the adsorption phenomenon better than the Freundlich model, proving the aggregation in solution followed by adsorption of the aggregates into the crystals. We believe that this study will be useful for protein encapsulation through CaCO3 crystals using the COS method.
CRIS-Team Scopus Importer:2021-06-08

Vaterite-based in situ surface modification and process-dependent biocompatibility of laser sintered polypropylene - Schlicht, Samuel; Campbell, Jack Charlie; Weber, Alexander Christian; Westhoff, Jan; Volodkin, Dmitry; Fischer, Dagmar; Drummer, Dietmar; Vikulina, Anna (Journal of Materials Research and Technology, 2024)
Polypropylene (PP) rapidly gains scientific attention as fatigue-resistant and lightweight tissue repair and implant material, while emerging laser-sintering based methods for PP processing further allow unlimited versatility of PP specimens and often reduced numbers of process steps, substituting traditional manufacturing approaches. Generally, PP is considered biocompatible for a variety of medical applications while showing superior long-term stability, however, thermoplastic processing of polypropylene may induce the formation of cytotoxic degradation products, necessitating its cytotoxicological assessment. In the present study, PP specimens have been fabricated using warm, quasi-isothermal and complementary cold, non-isothermal powder bed fusion (PBF), allowing processing PP at ambient powder bed temperature of 25 °C for minimizing thermal exposure and the formation of decomposition products. The surface of manufactured specimens has been modified with hybrid coatings consisting of mesoporous inorganic microcrystals of vaterite laden with model biomacromolecules, i.e., fluorescently labelled dextran, demonstrating the stable coating and attachment of dextran-loaded vaterite crystals independent of the applied PBF processing regime. Vaterite coating is degradable and enables the opportunity to endow the surface of PP with sustained release functionalities. Both coated and uncoated specimens demonstrated excellent biocompatibility independent of the applied processing regime, as evaluated in an ex ovo shell-less hen’s egg model.
Keywords: powder bed fusion; additive manufacturing; vaterite; drug release; hen’s egg model

Vaterite-nanosilver hybrids with antibacterial properties and pH-triggered release - Ferreira, Ana M.; Vikulina, Anna; Cave, G. W.V.; Loughlin, M.; Puddu, V.; Volodkin, D. (Materials Today Chemistry, 2023)
Silver nanoparticles (AgNPs) have been used for over a century in various applications due to their distinctive properties. Nonetheless, the poor stability of AgNPs and adverse effects on living organisms have driven the search for materials able to protect and better control their release. Vaterite CaCO3 crystals have been studied in the last two decades as carriers for different drugs due to their biocompatibility, easy synthesis and pH-sensitive properties. Herein, AgNPs were loaded into vaterite to protect, store, and control their release, resulting in CaCO3/AgNPs hybrids. To tune the release of the AgNPs, the recrystallization of the hybrids into thermodynamically more stable calcite was studied and modulated with carboxymethyl–dextran (DexCM) and poly(4-styrenesulfonic acid) sodium salt (PSS), with the last one being able to stabilise the hybrids and prevent a premature release of the AgNPs at low contents (2%, w/w). The release of AgNPs from the hybrids was studied at pH 5 to 9, showing a pH-dependent release suppression for PSS-stabilised hybrids. Various mathematical models were applied to clarify the release mechanism, confirming the role of PSS in stabilising and targeting the release of AgNPs. The antibacterial studies demonstrated that the hybrids protect the AgNPs without affecting their activity, with the released nanoparticles being effective against Escherichia coli, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa. Overall, this work sheds light on the release mechanisms of AgNPs from the inorganic hybrids helping to foresee the release profiles of other compounds from vaterite.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Calcium carbonate; Controlled release; Recrystallization; Sodium poly(4-styrenesulfonic acid) sodium salt

Vaterite vectors for the protection, storage and release of silver nanoparticles - Ferreira, Ana M.; Vikulina, Anna; Cave, Gareth W.V.; Loughlin, Michael; Puddu, Valeria; Volodkin, Dmitry (Journal of Colloid and Interface Science, 2023)
Silver nanoparticles (AgNPs) have found widespread commercial applications due to their unique physical and chemical properties. However, their relatively poor stability remains a main problem. An ideal way to improve the stability of AgNPs is not only to endow colloidal stability to individual nanoparticles but also to protect them from environmental factors that induce their agglomeration, like variation of ionic strength and pH, presence of macromolecules, etc. Mesoporous calcium carbonate vaterite crystals (CaCO3 vaterite) have recently attracted significant attention as inexpensive and biocompatible carriers for the encapsulation and controlled release of both drugs and nanoparticles. This work aimed to develop an approach to load AgNPs into CaCO3 vaterite without affecting their properties. We focused on improving the colloidal stability of AgNPs by using different capping agents, and understanding the mechanism behind AgNPs loading and release from CaCO3 crystals. Various methods were applied to study the AgNPs and CaCO3 crystals loaded with AgNPs (CaCO3/AgNPs hybrids), such as scanning and transmission electron microscopy, X-ray diffraction, infrared and mass spectrometry. The results demonstrated that polyvinylpyrrolidone and positively charged diethylaminoethyl-dextran can effectively keep the colloidal stability of AgNPs during co-precipitation with CaCO3 crystals. CaCO3/AgNPs hybrids composed of up to 4 % weight content of nanoparticles were produced, with the loading mechanism being well-described by the Langmuir adsorption model. In vitro release studies demonstrated a burst release of stable AgNPs at pH 5.0 and a sustained release at pH 7.5 and 9.0. The antibacterial studies showed that these hybrids are effective against Escherichia coli, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa, three important bacteria responsible for nosocomial infections. The developed approach opens a new way to stabilise, protect, store and release AgNPs in a controlled manner for their use as antimicrobial agents.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Calcium carbonate; Dextran; Immobilisation; Polyvinylpyrrolidone; Vaterite

Which biopolymers are better for the fabrication of multilayer capsules? A comparative study using vaterite CaCO3as templates - Campbell, Jack; Abnett, Jordan; Kastania, Georgia; Volodkin, Dmitry; Vikulina, Anna S. (ACS Applied Materials and Interfaces, 2021)
The polymer layer-by-layer assembly is accounted among the most attractive approaches for the design of advanced drug delivery platforms and biomimetic materials in 2D and 3D. The multilayer capsules can be made of synthetic or biologically relevant (e.g., natural) polymers. The biopolymers are advantageous for bioapplications; however, the design of such "biocapsules"is more challengeable due to intrinsic complexity and lability of biopolymers. Until now, there are no systematic studies that report the formation mechanism for multilayer biocapsules templated upon CaCO3 crystals. This work evaluates the structure-property relationship for 16 types of capsules made of different biopolymers and proposes the capsule formation mechanism. The capsules have been fabricated upon mesoporous cores of vaterite CaCO3, which served as a sacrificial template. Stable capsules of polycations poly-l-lysine or protamine and four different polyanions were successfully formed. However, capsules made using the polycation collagen and dextran amine underwent dissolution. Formation of the capsules has been correlated with the stability of the respective polyelectrolyte complexes at increased ionic strength. All formed capsules shrink upon core dissolution and the degree of shrinkage increased in the series of polyanions: heparin sulfate < dextran sulfate < chondroitin sulfate < hyaluronic acid. The same trend is observed for capsule adhesiveness to the glass surface, which correlates with the decrease in polymer charge density. The biopolymer length and charge density govern the capsule stability and internal structure; all formed biocapsules are of a matrix-type, other words are microgels. These findings can be translated to other biopolymers to predict biocapsule properties.
CRIS-Team Scopus Importer:2021-06-08
Keywords: calcium carbonate; hard templating; multilayer; polyelectrolyte; sacrificial; vaterite